The Driving Behavior Survey as a Measure of Behavioral Stress Responses to MVA-Related PTSD - Baker, Aaron S. (2014)
Numerous treatments are available that address the core symptoms of posttraumatic stress disorder (PTSD). However, there are a number of related behavioral stress responses that are not assessed with PTSD measures, yet these behavioral stress responses affect quality of life. The goal of the current study was to investigate whether a recently developed measure of behavioral stress response, the Driving Behavior Survey (DBS), was sensitive to change associated with treatment among a group of participants diagnosed with PTSD. The DBS indexes anxious driving behavior, which is frequently observed among individuals with motor vehicle accident-related PTSD. Participants (n = 40) were racially diverse adults (M age = 40.78, 63% women) who met diagnostic criteria for motor vehicle accident-related PTSD. Hierarchical linear modeling analyses indicated that participants who were assigned to a brief, exposure-based intervention displayed significant reductions on the DBS subscales relative to participants assigned to the wait-list control condition (r = .41–.43). Moreover, mediational analyses indicated that the observed reductions on the DBS subscales were not better accounted for by reductions in PTSD. Taken together, these findings suggest that the DBS subscales are sensitive to changes associated with PTSD treatment and can be used to augment outcome assessment in PTSD treatment trials.